2002
DOI: 10.1007/s00041-002-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Linear Approximation and Reproduction of Polynomials by Wilson Bases

Abstract: Wilson bases are constituted by trigonometric functions multiplied by translates of a window function with good time frequency localization. In this article we investigate the approximation of functions from Sobolev spaces by partial sums of the Wilson basis expansion. In particular, we show that the approximation can be improved if polynomials are reproduced. We give examples of Wilson bases, which reproduce linear functions with the lowest-frequency term only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[9,11,12,14]). For some applications (e.g., in image compression) it is important that a smooth function has a good local approximation by using a very small number of terms, i.e., using only small indices k in (2.6).…”
Section: Reproduction Of Modulated Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,11,12,14]). For some applications (e.g., in image compression) it is important that a smooth function has a good local approximation by using a very small number of terms, i.e., using only small indices k in (2.6).…”
Section: Reproduction Of Modulated Polynomialsmentioning
confidence: 99%
“…For some applications (e.g., in image compression) it is important that a smooth function has a good local approximation by using a very small number of terms, i.e., using only small indices k in (2.6). In this case, the reconstruction of polynomials by only the low frequency elements of the Wilson bases is of essential importance (see [9,11,12]). The optimal case is that only the DC terms ψ 0 j , j ∈ Z, are necessary to represent polynomials up to a certain degree.…”
Section: Reproduction Of Modulated Polynomialsmentioning
confidence: 99%
“…If we choose a translate w = N m (· − y), y ∈ R, as a window for the Wilson system, we also have the polynomial reproduction property, namely each p ∈ m−1 has a representation p(x) = j a j ψ 0 2j (x), x ∈ R, for some coefficients a j . It is known from [11,12] that Wilson bases with this property have very good approximation properties.…”
Section: B-splines As Window Functionsmentioning
confidence: 99%
“…Wilson bases without the two-overlapping restriction have been investigated by several authors [8,11,16,17,19]. In [12], window functions which reproduce linear functions with only the first frequency term were constructed, allowing the overlap of three windows at the same time. In [9,11,12], it has been shown that the reproduction of polynomials results in very good approximation properties.…”
Section: Introductionmentioning
confidence: 99%
“…e e and Meyer [24] and the Wilson bases of Daubechies et al [12]. Approximation properties of such bases have been investigated in [2,4].…”
Section: Introductionmentioning
confidence: 99%